Oral health in the analysis of patients with hearing disabilities - Almeida, Janaína Rocha de Sousa; Leite, Carina de Mesquita; Holanda, Kátia de Gois Saldanha; Calvasina, Paola; Franco, Jéferson Martnins Pereira Lucena; Silva, Paulo Goberlânio Barros (Journal of Health & Biological Sciences, 2021)
Objective: To assess the degree of knowledge of deaf and hard of hearing patients about oral health and relate it to clinical and demographic variables. Methods: The target population was schoolchildren from the 6th to the 9th grade of Elementary School and the 1st year of High School. Data collection took place through a structured questionnaire previously validated. The expressed as absolute and percentage frequencies it was analyzed using Fisher's exact test or Pearson's chi-square test (p <0.05). Results: Assessing the relationship between oral health and quality of life, to 53 students, 32.1% of students never reported pain in their teeth, mouth, or jaws, 55.8% never missed school due to problems with their teeth or dental treatments, 71, 2% never avoided smiling or laughing due to problems with teeth or dental treatments, 53.8% never avoided opening their mouths or talking due to problems with teeth or dental treatments. Conclusion: Professional and patient communication should be emphasized with the deaf and hard of hearing to intensify the importance of monitoring with the dental surgeon, carrying out activities to promote, prevent, cure, and rehabilitate oral health.